Pengembangan Limbah Kulit Pisang Sebagai Alternatif Pembuatan Ice Cream Untuk Peningkatan Daya Saing UMKM Desa Pasirsari - Muhamad Syahwildan; Indra Setiawan (IKRA-ITH ABDIMAS, 2023)
This journal describes the results of community service activities carried out at Pelita BangsaUniversity in the form of Empowerment of Micro, Small and Medium Enterprises (MSMEs)in the field of Administration and Marketing in Pasirsari Village, South Cikarang. Thebackground of this activity is based on a field survey where many MSMEs do not have a NIB,product logo and lack of knowledge to register their business on google maps. The priorityproblem is that MSMEs in the Pasirsari Village area are immigrants so that few of them havecomplete data such as domicile letters and NPWP. The solution and method in this serviceprogram is to create a strategy in an effort to empower MSMEs through Making a BusinessIdentification Number (NIB), making product logos, as well as registering google maps andmaking Banana Peel Ice Cream SMEs. The expected outputs from this activity are 1) MSMEsin the Pasirsari area can have a Business Identification Number and understand its benefitsand functions. 2) MSMEs in the Pasirsari area can have a product logo as a business identityand the business location has been registered on google maps to make it easier for visitorsto find a business location 3) MSME Banana Peel Ice Cream can be developed and passedon by one of the MSMEs in Pasirsari Village and is expected to become a characteristicproduct Pasirsari Village. This makes MSME actors who were previously affected by thepandemic are now starting to rise again, sales that previously experienced a decline are nowstarting to return to normal, people who previously did not understand social media and Ecommerceare now technologically literate because of their previous virtual habits, MSMEsare trying to get up. back by promoting on social media and registering their business to Ecommerce,people who are used to buying goods online because shops that were forced toclose because they can only sell virtual or take away are now back in operation. With“Banana Peel Ice Cream "The ice cream is inspired by a brand that has banana flavored icecream. Finally, we have the idea to make the same ice cream but made from banana peels,besides the vitamins contained in banana peels, we also hope that this Banana Peel IceCream can reduce food waste, as banana peels are food waste.